External validation of the SCARE score in identifying acute coronary syndromes during medical regulation of chest pain - Lemoine Augustine; Fontaine Xavier; Duval Camille; Quirin Mathilde (BMC Emergency Medicine)
Abstract Background Medical regulation of chest pain is challenging due to the multitude of potential diagnoses. The key challenge is to avoid misdiagnosing acute coronary syndrome while preventing over-triage. The SCARE score (based on age, sex, smoking, typical coronary pain, inaugural pain, sweats, and dispatcher’s conviction) classifies patients as low, intermediate, or high risk of acute coronary syndrome. This study aimed to determine the diagnostic performance of the SCARE score among patients calling with chest pain. Methods This single-center prospective study was conducted at the Charleville-Mézières Emergency Medical Communication Centre. Data collection included standardized questionnaires and call tape reviews. The SCARE score was compared with final diagnoses from medical records. Results From October 2 to November 16, 2023, 194 patients were included, with 32 (16%) diagnosed with acute coronary syndrome. Of these, 24 patients (75%) were managed by a prehospital medical team. The AUROC for the SCARE score was 0.80 [95% CI 0.73—0.87]. At a low-risk threshold (26), sensitivity was 100% [95% CI 89—100] and specificity was 45% [95% CI 37—53]. At a high-risk threshold (36), sensitivity was 72% [95% CI 53—86] and specificity was 70% [95% CI 63—77]. Conclusion The SCARE score exhibited excellent sensitivity and overall acceptable performance in predicting acute coronary syndrome in patients calling with non-traumatic chest pain. Trial registration ID-RCB 2023-A01672-43.